PERANCANGAN COFFEE-TABLE BOOK TENTANG OBJEK WISATA DI WILAYAH GARUT SELATAN - PRIMA GUMILANG; CHRISTINE CLAUDIA LUKMAN; HENDRA SETIAWAN (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
Southern Garut is one of the potential tourist attractions in the Garut region. On the way to southern Garut, tourists will be able to enjoy wonderful sceneries, such as the mountain, waterfall, and beach. The local government supports the tourism by fixing the route to this southern area. Nevertheless, it is not a well-known area so that it rarely becomes a destination of the tourists.One effort to introduce Southern Garut to Javanese urban society is through the creation of a coffee table book design (print book and e-book). This book will reveal the sides of Southern Garut rarely visited by the Javanese urban society. This book may become a representation of Southern Garut so that the target audience can see its beauty, and in the end they would decide to make it their destination. Design created is based on the concept derived from the data analysis collected through field observation, structured & unstructured interviews, and questionnaires to 100 respondents. The literature study was also used to support the data obtained from the field. The photographs in this book are the chief medium, which will show the pictures of Southern Garut landscape. This book is meant to become a means of information for those who have not yet enjoyed the beauty of Southern Garut.Â Keywords: coffee-table book; southern Garut; tourism